Influence of human resources, government internal control system, and information technology utilization on financial statement quality of Bengkulu city government’s / Dri Asmawanti S ...[et al.] - -, Dri Asmawanti S; -, Shinta Juliana; -, Baihaqi; -, Nila Aprila (UiTM Cawangan Johor, 2019)
The aim of this study was to determine the influence of human resources, government internal control system, and information technology utilization on the quality of financial statements in Bengkulu City regional government. The population used in this study were all Regional Organizations Apparatus (OPD) of Bengkulu City and the census method was applied for sampling. Primary data used were obtained by distributing questionnaires to each OPD and the research was conducted through the application of a quantitative approach. The results showed human resources, government internal control system, and the information technology utilization have a positive influence on the quality of Bengkulu City regional government’s financial statements.